Ordonnance concernant les fabriques de savon : du 10 octobre 1751 : à Monseigneur de Guiganrd, Vicomte de Saint Preist, Maître des Requêtes, Intendant en Languedoc - Saint-Priest, Jean Emmanuel de Guignard, vicomte de, 1714-1785 ([publisher not identified], 1751)
Request of Alexandre Derbaud to standardize recordkeeping in soap factories. Includes law establishing such practices.